Monte carlo simulation of heterotypic cell aggregation in nonlinear shear flow - Jiakou Wang; Margaret J. Slattery; Meghan Henty Hoskins; Shile Liang; Cheng Dong; Qiang Du (Mathematical Biosciences and Engineering)
In this paper, we develop a population balance model for cell aggregationand adhesion process in a nonuniform shear flow. Some Monte Carlosimulation results based on the model are presented for the heterotypic cell-cellcollision and adhesion to a substrate under dynamic shear forces. In particular,we focus on leukocyte (PMN)-melanoma cell emboli formation and subsequenttethering to the vascular endothelium (EC) as a result of cell-cell aggregation.The simulation results are compared with the results of experimental measurement.Discussions are made on how we could further improve the accuracy ofthe population balance type modelling.